A study of factors that influence health insurance coverage towards employees at Petronas Carigali Sdn Bhd / Nurhamidah Hizam - Hizam, Nurhamidah (Faculty of Business and Management, 2015)
This research aims to study the factors that influence health insurance coverage towards employees at Petronas Carigali Sdn Bhd. The selected variables will be analyzed to discover the factors that contribute to health insurance coverage in Petronas Carigali Sdn Bhd. This research paper consists of two variables which are dependent variable and independent variable. The variables that the researcher investigates are health insurance, employer responsibility, cost of health insurance, preferences and employees understanding. The data obtained are be treated as primary as the researcher use questionnaires to obtain the required information from the respondents. Other than that, some of the related information was obtained from the secondary data such as internet, journals and book. The variables will be analyzed by using the frequency distribution, descriptive analysis, reliability analysis, and multiple regression analysis. Computer Software of Statistical Package for Social Science is used in order to analyze the data. The findings indicate that employees understanding are the most influencing factor that influences the health insurance coverage towards employees at Petronas Carigali Sdn Bhd followed by the preferences, cost of health insurance and employer responsibility. The findings also show that although the cost of health insurance has a negative relationship with the health insurance, it still has significant relationship with the health insurance. The researcher also has come out with few recommendations to be taken into consideration. By implementing these recommendations, it will help the employees to buy the health insurance coverage and benefit of it in the future.